Accounting Conservatism and Ownership Structure Effect: Evidence from Industrial and Financial Jordanian Listed Companies - Alkordi, Amneh; Al-Nimer, Munther; Dabaghia, Mouhammad (International Journal of Economics and Financial Issues, 2017)
This study aims to examine the impact of ownership structure on the level of accounting conservatism in Jordan by using a sample of 99 manufacturing and financial companies listed on the Amman Stock Exchange between 2005 and 2013. On one hand, ownership structure was measured by: foreign; governmental; institutional; and concentration of ownership. On the other hand, accounting conservatism was measured by accrual-based measures. This study used the Ordinary Least Square (OLS) method was as the multiple regression analysis. It was found that three of the independent variables were significant and one was not. The study’s findings show that there is an inverse effect of governmental ownership on accounting conservatism. In contrast, the study indicates a significant and positive relationship between foreign and institutional ownership with accounting conservatism but the concentration of ownership doesn’t affect conservatism. Based on these results, this paper provides some insights for the extant literature in this field and, for interested parties, conveys some conservatism policy implications. Additionally, this study will open doors for researchers to look at accounting conservatism in detail. Keywords: accounting conservatism; ownership structure; Amman Stock Exchange JEL Classifications: G31, M41